2014
DOI: 10.1080/00480169.2014.940410
|View full text |Cite
|
Sign up to set email alerts
|

Introducing breathlessness as a significant animal welfare issue

Abstract: Breathlessness is a negative affective experience relating to respiration, the animal welfare significance of which has largely been underestimated in the veterinary and animal welfare sciences. In this review, we draw attention to the negative impact that breathlessness can have on the welfare of individual animals and to the wide range of situations in which mammals may experience breathlessness. At least three qualitatively distinct sensations of breathlessness are recognised in human medicine--respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 53 publications
0
112
0
Order By: Relevance
“…The drowning process is complex, involving sequential, concurrent and overlapping cardiorespiratory reflexes, electrolyte and blood gas abnormalities, aspiration and swallowing of liquid, vomition, struggling, involuntary movements and physical exhaustion, breathlessness, or ''air-hunger'' 4 eventually culminating in death. 7 The central mechanism of drowning is rapid and persistent hypoxemia following the introduction of liquid at the entrance of the airway.…”
Section: The Process and Mechanism Of Drowningmentioning
confidence: 99%
“…The drowning process is complex, involving sequential, concurrent and overlapping cardiorespiratory reflexes, electrolyte and blood gas abnormalities, aspiration and swallowing of liquid, vomition, struggling, involuntary movements and physical exhaustion, breathlessness, or ''air-hunger'' 4 eventually culminating in death. 7 The central mechanism of drowning is rapid and persistent hypoxemia following the introduction of liquid at the entrance of the airway.…”
Section: The Process and Mechanism Of Drowningmentioning
confidence: 99%
“…The aversive behaviours are considered a response to the CO 2 that causes irritation of nasal mucosal membranes and the fact that CO 2 is a strong respiratory stimulation that is known to induce a sense of breathlessness prior to loss of consciousness in humans Schwartzstein, 1995, Raj, 2006). It may thus form a serious concern for animal welfare, as breathlessness is considered unpleasant for the animal (Beausoleil and Mellor, 2015). Barfod (1990) and Erhardt et al (1989) on the other hand did not find conclusive evidence that CO 2 irritates the membranes and concluded that the observed gasping is not a sign of respiratory distress, but merely a normal response to the excessive CO 2 in the body.…”
Section: Gradual Loss Of Consciousness Co 2 Stunningmentioning
confidence: 98%
“…Figure 3 shows that gasping occurred closely in time with retreat attempts. It may be assumed that gasping does compromise animal welfare in conscious pigs, because it is associated with a sense of breathlessness (Beausoleil and Mellor, 2015). Muscular contractions are observed in the majority of pigs exposed to high CO 2 concentrations and it has been heavily debated whether they occur before or after animals have lost consciousness.…”
Section: Dotted Lines Indicate Average Values Of All Observations Amentioning
confidence: 99%
See 2 more Smart Citations